Ovariohysterectomy and Partial Vaginectomy for Treatment of Cervicovaginitis in a Dog - Christian A. Folk; Cassie N. Lux; Whitney DeGroot (Case Reports in Veterinary Medicine)
A 1-year-old sexually intact female Labrador Retriever was evaluated for malodorous vaginal discharge, lethargy, and vomiting. A diagnosis of pyometra was suspected based on signalment, clinical signs, and abdominal ultrasonography. The dog underwent an exploratory celiotomy revealing a palpably enlarged cervix and edematous, fluid-filled vagina with an otherwise normal uterus. The ovaries, uterus, cervix, and cranial vagina were surgically resected. Histopathology revealed mild to moderate regionally extensive subacute neutrophilic cervicovaginitis due to an unknown underlying etiology. The dog did not exhibit any postoperative complications or recurrence of clinical signs in 6 months. This case represents an unusual disease condition, which presented in a manner typical for pyometra, yet required more extensive surgical resection.